Multiaxial Fatigue Life Prediction on S355 Structural and Offshore Steel Using the SKS Critical Plane Model. - Sánchez-Cruces, Manuel Alejandro; López-Crespo, Pablo; Moreno-Morales, María Belén; Antunes, Fernando Ventura; Antunes, Fernando Ventura (MDPI, 2018)
This work analyses the prediction capabilities of a recently developed critical plane model, called the SKS method. The study uses multiaxial fatigue data for S355-J2G3 steel, with in-phase and 90◦ out-of-phase sinusoidal axial-torsional straining in both the low cycle fatigue and high cycle fatigue ranges. The SKS damage parameter includes the effect of hardening, mean shear stress and the interaction between shear and normal stress on the critical plane. The collapse and the prediction capabilities of the SKS critical plane damage parameter are compared to well-established critical plane models, namely Wang-Brown, Fatemi-Socie, Liu I and Liu II models. The differences between models are discussed in detail from the basis of the methodology and the life results. The collapse capacity of the SKS damage parameter presents the best results. The SKS model produced the second-best results for the different types of multiaxial loads studied.
Keywords: Acero - Fatiga; Ciencia de los materiales; S355-J2G3; Critical plane model; Multiaxial fatigue; Non-proportional